Relative position control and coalescence of independent microparticles using ultrasonic waves - Deng, Shuang (2017)
Controlling the relative positions and coalescence of independent cells or microparticles is of particular importance for studying many physical phenomena, biological research, pharmaceutical tests, and chemical material processing. In this work, contactless maneuvering of two independent microparticles initially lying on a rigid surface was performed at a stable levitation height within a water-filled ultrasonic chamber. Three lead zirconate titanate transducers with 2 MHz thickness resonance frequency were obliquely mounted in a homemade device to form a sound field in a half space. By modulating the excitation voltage of a single transducer and the subsequent combination of amplitude and phase modulation, two separate 80 μm diameter silica beads were picked up from the chamber bottom, approached, and then coalesced to form a cluster in different ways. Both particles simultaneously migrated towards each other in the former process, while more dexterous movement with single-particle migration was realized for the other process. There is good agreement between the measured trajectories and theoretical predictions based on the theory of the first-order acoustic radiation force. The method introduced here also has the ability to form a cluster at any desired location in the chamber, which is promising for macromolecule processing ranging from the life sciences to biochemistry and clinical practice.